2008
DOI: 10.1682/jrrd.2007.01.0020
|View full text |Cite
|
Sign up to set email alerts
|

Automating activity-based interventions: The role of robotics

Abstract: Abstract-We have seen a continued growth of robotic devices being tested in neurorehabilitation settings over the last decade, with the primary goal to improve upper-and lowermotor function in individuals following stroke, spinal cord injury, and other neurological conditions. Interestingly, few studies have investigated the use of these devices in improving the overall health and well-being of these individuals despite the capability of robotic devices to deliver intensive timeunlimited therapy. In this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 31 publications
1
27
0
1
Order By: Relevance
“…This is consistent with issues raised in the literature concerning the disadvantage of technologically advanced interventions lacking human touch and the ''same feel as therapists do'' [56]. Our results can inform thinking about the role that therapeutic relationship plays in the delivery of technology-based interventions within a child and family-centered care context.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with issues raised in the literature concerning the disadvantage of technologically advanced interventions lacking human touch and the ''same feel as therapists do'' [56]. Our results can inform thinking about the role that therapeutic relationship plays in the delivery of technology-based interventions within a child and family-centered care context.…”
Section: Discussionsupporting
confidence: 88%
“…Promising results with regard to cardiovascular effects of robot-assisted therapy have been reported in the population with SCI [22][23][24][25]. A recent cross-sectional study by Jack et al showed that, with vigorous active participation of patients, a substantial increase in heart rate (HR) and oxygen consumption (V O 2 ) can be achieved [24].…”
Section: Introductionmentioning
confidence: 99%
“…Gait training is operator dependent and requires highly trained therapists utilizing a standardized technique that suffers from significant inter-practitioner variance; FES is delivered by a robotic device, ensuring repetitive accuracy. Robotic gait training devices have been built: the Lokomat and Pediatric Lokomat (Hocoma AG, Switzerland), the Autoambulator (HealthSouth, Birmingham, AL), REOAmbulator (Motorika Ltd.) but in clinical practice they do not yet deliver the same results like therapist guided gait training [Edgerton and Roy, 2009;Hidler et al, 2008].…”
Section: The Role Of Task Specific Training (Quality) and Spinal Centmentioning
confidence: 99%